Rehabilitation of Baricco`s and Japrisot`s Heroes in the Light of Modern Criticism - Petrović, Ljiljana Z. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
The paper observes the attempt to morally rehabilitate the soldiers executed in the First World War, which takes place on a literary level in the novels Questa storia (This Story) by Alessandro Baricco and Un long dimanche de fiançailles (A Very Long Engagement) by Sébastien Japrisot. The soldiers were punished twice: by taking their lives and by being stigmatized in the memory. A detailed analysis, relying on the theoretical propositions of Michel Foucault and René Girard, leads to the conclusion that the truth is exactly the opposite of what seems evident from the legal side. Through the prism of such a new and different view, the culprit and the victim change places; it is the state that represents the violent/punitive apparatus whose main motive of action is to acquire or maintain control and power, while the executed individuals are only its victims.
Keywords: culprit; victim; punishment; society; execution; control; power